Laboratory assessment of the effect of cattle slurry pre-treatment on organic N degradation after soil application and N2O and N2 emissions - Fangueiro, D. (2013)
Slurry separation using mechanical and chemical methods is one of the options considered to solve problems of slurry management at the farm scale. The fractions obtained with such treatments have distinct compositions, which allow different options for their utilization (composting, direct application, and fertigation). In this study, four fractions of slurry were obtained using a combined treatment system including slurry treatment with a screw press separator (solid and liquid fractions) followed by sedimentation with the addition of Polyacrylamide (PAM) (PAM-Supernatant and PAM-Sediment) to the LF. These fractions were then incorporated into arable soil under controlled laboratory conditions and the organic N degradation from each treatment was followed for 94 days. Total N emissions (N2O + N2 ) as well as the sources of the N emissions (nitriﬁcation or denitriﬁcation) were also studied during this period. Results showed that the slurry fractions (SFs) had distinct behavior relative to the whole slurry (WS), namely in terms of N degradation in soil, where N mineralization was observed only in the WS treatment whereas N immobilization occurred in the other treatments. In terms of N2O emissions, higher losses, expressed as a percentage of the total N added, occurred from the LF treatments (liquid, PAM-Supernatant and PAM-Sediment). This work indicates that the slurry treatment by mechanical and chemical separation may be a good option for slurry management at the farm scale since it allows greater utilization of the different fractions with a small effect on N2O emissions after SFs’ application to soil